2021
DOI: 10.51817/jas.v2i2.39
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Learning Motivation Using Schoology as Online Learning at SMPN 03 Mukomuko

Abstract: This study aims to describe how is the students’ learning motivation using Schoology as an online learning during COVID-19 at SMPN 03 Mukomuko. The participants in this study is students in eight grade for academic year 2020/2021 with a total 134. To collect the data researcher used questionnaire and interview that related to students’ learning motivation using Schoology as the intrumentations. Based on this research, there are two types of students’ motivation in learning, namely intrinsic and extrinsicmotiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…H6 is confirmed, indicating that a positive influence of learning motivation on critical thinking awareness. Previous research has demonstrated that increased motivation for learning is associated with higher levels of critical thinking, whereas decreased motivation for learning is linked to lower levels of critical thinking [35], meanwhile, intrinsic learning motivation drives student engagement in academic activities [146,147]. When students are interested and motivated to learn, they actively participate in class, engage in additional reading, and enthusiastically join discussions.…”
Section: The Significant Impact Of Learning Motivation On Critical Th...mentioning
confidence: 99%
“…H6 is confirmed, indicating that a positive influence of learning motivation on critical thinking awareness. Previous research has demonstrated that increased motivation for learning is associated with higher levels of critical thinking, whereas decreased motivation for learning is linked to lower levels of critical thinking [35], meanwhile, intrinsic learning motivation drives student engagement in academic activities [146,147]. When students are interested and motivated to learn, they actively participate in class, engage in additional reading, and enthusiastically join discussions.…”
Section: The Significant Impact Of Learning Motivation On Critical Th...mentioning
confidence: 99%